Crisis communication in a blackout scenario - An assessment considering socio-spatial parameters and the vulnerabilities of the population. (1st April 2022) - Rudolph-Cleff, Annette; Knodt, Michèle; Schulze, Joachim; Engel, Alice
Abstract: Electrical energy is the bloodline of the modern world. Especially the densely populated urban areas of cities have a strong dependency on the steady flow of energy in order for infrastructures to supply residents, businesses and industries. But what if this necessity is disrupted in a blackout? Many actions that can be taken in preparation for or in the wake of a power failure cannot be universal but must be tailored. This can relate to the specific demographics and socio-economics of any given city district. The goal of a contextual approach to emergency response measures is to prioritize help for those who are especially vulnerable to the event. Crisis communication is known to be a decisive factor that has the potential to unfold a de-escalating effect and is highly receptive for a tailored approach. This is even more important when one is talking about a long-term power failure because nearly all common channels of communication eventually fail. Research in this paper emphasizes on the topic of crisis communication in three ways: 1) it assesses and maps residents that are highly vulnerable in a blackout, 2) derives crisis communication requirements corresponding to these vulnerabilities and 3) evaluates a new possible channel of crises communication, namely utilizing so called Out-of-Home advertising units. These are advertising billboards widely distributed in the city that are seeing prototypical use for ad hoc crisis warning dissemination in selected German cities. The assessment is based on the case study of the city of Darmstadt, Germany.